Sensoriamento de temperatura por alargamento de banda baseado em microcristais de BaTiO3: Nd3+ - Espíndola, Lauro Oliveira (2024)
In this work, samples of micrometric rod-shaped crystals of BaTiO3 doped with 0.5; 1; 2 e 3 mol% of Nd3+ were evaluated as luminescent thermometers. The emission spectra for luminescent thermometry were collected in a temperature range of 303 and 373 K, with the sample being excited with a CW diode laser of 800 nm with power of 5.0 mW. The thermometric parameters used for the analysis of luminescent thermometry through spectral broadening were the Effective Width and the Full Width at Half Maximum (FWHM). The best results obtained for relative sensitivity were 0, 389% K−1 through the Effective Width with the sample doped with 1 mol% of Nd3+ and 0, 489% K−1 through FWHM with the sample doped with 0, 5 mol% of Nd3+. The results obtained for the spectral broadening methods demonstrate excellent reproducibility, repeatability, relative sensitivity and temperature uncertainty for samples of 1, 2 and 3 mol% of Nd3+, however, the repeatability result for the 0, 5 mol% of Nd3+ was not satisfactory.